Transforming global public health: Climate collaboration, political challenges, and systemic change - Krzysztof Goniewicz; Frederick M. Burkle; Amir Khorram-Manesh (Journal of Infection and Public Health)
Amidst the global challenges of the 21st century, an urgent call emerges to redefine global public health in response to the multifaceted threats of climate change, political denial, and systemic barriers. This study employs a critical analysis approach, combining a narrative literature review with Action Research, to assess the health impacts of climate change and identify pathways for resilience. Direct and indirect implications—ranging from heat-related illnesses and vector-borne diseases to mental health challenges and displacement—are highlighted, alongside barriers posed by governance structures and economic disparities. A novel collaborative framework, CLIMBED COOL, is introduced, emphasizing adaptation, transformation, and transition as key strategies to address these challenges. Findings also underscore the importance of robust education, simulation-based training, and structured data-sharing mechanisms through regional Centers for Disease Control and Prevention and global databases. This study advocates for a paradigm shift in global governance and collaboration, ensuring holistic and sustainable solutions for future generations.